Design of S‐Allylcysteine in Situ Production and Incorporation Based on a Novel Pyrrolysyl‐tRNA Synthetase Variant. (30th November 2016) - Exner, Matthias P.; Kuenzl, Tilmann; To, Tuyet Mai T.; Ouyang, Zhaofei; Schwagerus, Sergej; Hoesl, Michael G.; Hackenberger, Christian P. R.; Lensen, Marga C.; Panke, Sven; Budisa, Nediljko
Abstract: The noncanonical amino acid S ‐allyl cysteine (Sac) is one of the major compounds of garlic extract and exhibits a range of biological activities. It is also a small bioorthogonal alkene tag capable of undergoing controlled chemical modifications, such as photoinduced thiol‐ene coupling or Pd‐mediated deprotection. Its small size guarantees minimal interference with protein structure and function. Here, we report a simple protocol efficiently to couple in‐situ semisynthetic biosynthesis of Sac and its incorporation into proteins in response to amber (UAG) stop codons. We exploited the exceptional malleability of pyrrolysyl‐tRNA synthetase (PylRS) and evolved an S ‐allylcysteinyl‐tRNA synthetase (SacRS) capable of specifically accepting the small, polar amino acid instead of its long and bulky aliphatic natural substrate. We succeeded in generating a novel and inexpensive strategy for the incorporation of a functionally versatile amino acid. This will help in the conversion of orthogonal translation from a standard technique in academic research to industrial biotechnology. Abstract : A biochemical pathway for production of proteins containing S ‐allylcysteine : In vivo site‐specific protein olefination with S‐allylcysteine (Sac), produced in situ from allyl thiol, is possible with a novel pyrrolysyl‐tRNA synthetase capable of accepting a small substrate. The S‐allyl group is suitable as a minimal tag in different bio‐conjugations settings.